Dynamics of weak-magnetic-shear-sustained internal transport barrier during supersonic molecular-beam injection in JT-60U. (13th January 2021) - Kin, F.; Yoshida, M.; Takenaga, H.; Honda, M.; Tamura, N.; Narita, E.; Kamiya, K.; Bando, T.; Wakatsuki, T.; Isayama, A.
Abstract: The characteristics of ion heat transport inside the internal transport barrier (ITB), which is sustained by weak magnetic shear, are investigated using a cold pulse induced by supersonic molecular-beam injection (SMBI) in JT-60U. It is known that cold-pulse propagation in ITBs usually significantly reduces the temperature and degrades the temperature gradient. When subsequent SMBIs are launched before the temperature has recovered, it is observed that the temperature gradient of the ITB is not monotonically decreased but alternately decreased and increased. Alternating decreasing and increasing phases of the ITB temperature gradient continue for about 1 s (∼6 τ E ), and the properties of the cold-pulse propagation and the flux-gradient relations differ according to the phase. The usual transient transport analysis is also provided by inducing a cold pulse in stationary ITBs. A rapid reduction and recovery of the temperature is observed inside the ITBs, and it is found that the ion-heat flux changes without a variation in the local ion-temperature gradient or a change to the other observable local parameters. The flux-gradient relations exhibit significant hysteresis in two ITB cases: (i) ITBs with strong electron-density gradients and (ii) ITBs with weak ion-temperature gradients. In addition, the range in which hysteresis appears is most likely to depend on the width of the ITB.